Upaya Meningkatkan Kemampuan Bercerita Siswa pada Mata Pelajaran Bahasa Indonesia melalui Media Boneka Jari di Kelas III SDN 75/VII Kasang Melintang - Dinda Okta; Ika aryastuti Hasanah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research was motivated by the low storytelling ability of Class III students at SDN 75/VII Kasang Malintang. The purpose of this research is to determine the improvement in students' storytelling abilities in Indonesian Language Subjects through Finger Puppet Media in Class III of SDN 75/VII Kasang Melintang. This research is a classroom action research consisting of two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were Class III students at SDN 75/VII Kasang Melintang. This research was carried out in the second semester of the 2024/2025 academic year in Class III of SDN 75/VII Kasang Melintang. The results of this research are as follows (1) Efforts to improve students' storytelling abilities in Indonesian language subjects through finger puppet media in class III SDN 75/VII Kasang Melintang are carried out through the learning planning stage which includes preparing teaching modules, finger puppet media, observation instruments, and storytelling ability tests. The implementation stage includes the implementation of storytelling learning using finger puppets. In the first meeting of each cycle, students tell stories in groups, and in the second meeting of each cycle, students tell stories individually. The final stage is an evaluation carried out by testing students' storytelling abilities and assessed based on assessment guidelines. (2) an increase in students' storytelling abilities resulted in an increase in teacher activity from cycle I and cycle II with an average score of 76.65 to 90 in the "Very Good" category.